2013
DOI: 10.1038/nature12633
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent regulation of flowering by antagonistic FLM variants

Abstract: The appropriate timing of flowering is crucial for plant reproductive success. It is therefore not surprising that intricate genetic networks have evolved to perceive and integrate both endogenous and environmental signals, such as carbohydrate and hormonal status, photoperiod and temperature. In contrast to our detailed understanding of the vernalization pathway, little is known about how flowering time is controlled in response to changes in the ambient growth temperature. In Arabidopsis thaliana, the MADS-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
492
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 396 publications
(514 citation statements)
references
References 35 publications
19
492
0
3
Order By: Relevance
“…For example, SVP complexes with FLOWERING LOCUS C (FLC) to permit flowering only once FLC levels are sufficiently reduced by progressive chromatin changes in response to prolonged vernalization (Michaels and Amasino, 1999;Bastow et al, 2004;Sung and Amasino, 2004;Li et al, 2008). In addition, repressive complexes of SVP with FLOWERING LOCUS M or MADS AFFECTING FLOWERING2 decline at warmer temperatures, contributing to thermoresponsive flowering (Ratcliffe et al, 2003;Gu et al, 2013;Lee et al, 2013;Posé et al, 2013;Airoldi et al, 2015;Sureshkumar et al, 2016).…”
mentioning
confidence: 99%
“…For example, SVP complexes with FLOWERING LOCUS C (FLC) to permit flowering only once FLC levels are sufficiently reduced by progressive chromatin changes in response to prolonged vernalization (Michaels and Amasino, 1999;Bastow et al, 2004;Sung and Amasino, 2004;Li et al, 2008). In addition, repressive complexes of SVP with FLOWERING LOCUS M or MADS AFFECTING FLOWERING2 decline at warmer temperatures, contributing to thermoresponsive flowering (Ratcliffe et al, 2003;Gu et al, 2013;Lee et al, 2013;Posé et al, 2013;Airoldi et al, 2015;Sureshkumar et al, 2016).…”
mentioning
confidence: 99%
“…We used model 3 to predict the flowering times for various mutations at 16 • C, 23 • C and 27 • C and compared these with available experimental data [Pose13]. Loss of temperature dependence is seen both in experiment and in prediction of the FLM knockout.…”
Section: Application: Modeling Mutationsmentioning
confidence: 99%
“…Expression time series (qPCR) of FLM-β and FLM-δ at 23 • C, as well as relative expression of these splice variants after 10 days at 16 • C, 23 • C and 27 • C were obtained from [Pose13]. The equation describing how FLM-β and FLM-δ concentrations change with temperature was approximated by a linear fit between these data points.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…23 Previous studies have shown that the MADS-box TF genes FLOWERING LOCUS M (FLM), MADS AFFECTING FLOWERING 2 (MAF2) and SHORT VEGETATIVE PHASE (SVP) play key roles in the temperature-dependent regulation of flowering, with the alternative splicing of FLM and MAF2 working as a molecular thermometer to prevent or induce precocious flowering. 24,25 Alice Pajoro, postdoc in Richard Immink's group (Wageningen University, The Netherlands), reported her work on the epigenetic regulation behind this temperature-mediated alternative splicing process. Using RNA-seq, numerous temperature-mediated alternative splicing events, including many flowering time regulators, were identified.…”
Section: Microscopy Molecules and Modeling: Elucidating Nuclear Orgmentioning
confidence: 99%